Analisis Risiko Paparan Debu Kapas Terhadap Kejadian Bisinosis di Industri Tekstil PT. Grandtex Bandung - Mulyati, Sri Slamet; Setiani, Onny; Raharjo, Mursid (Jurnal Kesehatan Lingkungan Indonesia, 2015)
Background: Byssinosis is still health problems associated with exposure to cotton dust. High risk of health problems in Environmental Health Risk Assessment is expressed as a Risk Quotenit (RQ) .Work activities, the use of personal protective equipment, and psychological disorder may also affect the incidence of byssinosis. Methods: This was an observational research with cross sectional design. The population in this research are all employees of PT.Grandtex.Eighty workers from morning shifts only were randomly selected. Each worker was examined of the FEV1 and FVC. Questionnaires structured was another tools for collecting data.Total dust measured in the working environments and ambient air.Results: The results by Chi-Square test showed significant relation between the Risk Quotenit (RQ) with byssinosis (p-value 0.043; PR 1,8 (95%CI : 0.95-3.52),have a significant relationship between work activities with byssinosis (p-value 0.035; PR 2.2 (95%CI : 0.86-5.85)have a significant relationship between the use of personal protective equipment with byssinosis (p-value 0.001; PR 2.9 (95%CI : 1.21-6.81) and have a significant relationship between psychological disorders with byssinosis (p-value 0.023; PR 1,7 (95%CI : 1.28-2.14)Conclusion: The number of worker with positive Byssinosis symptoms and abnormal lung function 15 people(18.75%) , positive Byssinosis symptoms and normal lung function 35people(43.75%)Â Keywords : Byssinosis, cotton dust, risk assessment